1987
DOI: 10.1002/jnr.490180108
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenergic sympathetic innervation of the spleen: II. Tyrosine hydroxylase (TH)‐positive nerve terminals form synapticlike contacts on lymphocytes in the splenic white pulp

Abstract: Immunocytochemistry was used to demonstrate tyrosine hydroxylase (TH)-positive profiles in the spleen of the adult Fischer 344 rat. At the light microscopic level, numerous varicose nerve profiles were seen in the white pulp, particularly surrounding the central arteries and their arteriole branches. At the electron microscopic level, varicosities were seen in close proximity to smooth muscle cells of the arteries, and directly abutting lymphocytes (presumable T-lymphocytes) of the nearby periarteriolar lympha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
131
0
1

Year Published

1990
1990
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(135 citation statements)
references
References 26 publications
(22 reference statements)
3
131
0
1
Order By: Relevance
“…Our data showed that TH ϩ fibers were present around the vasculature of splenic arteries in normal mice, with some extending into the PALS; our findings support the findings of others in rodents (13)(14)(15)(16). In contrast, SCID mice exhibited a significantly denser array of perivascular fibers, but fewer fibrous extension into the PALS.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our data showed that TH ϩ fibers were present around the vasculature of splenic arteries in normal mice, with some extending into the PALS; our findings support the findings of others in rodents (13)(14)(15)(16). In contrast, SCID mice exhibited a significantly denser array of perivascular fibers, but fewer fibrous extension into the PALS.…”
Section: Discussionsupporting
confidence: 90%
“…Extensive arrays of fibers also travel with the central artery and its arteriolar branches in the white pulp, and extend into the parenchyma of the periarteriolar lymphatic sheaths (PALS) that are rich in T cells (13,14). Electron microscopic studies revealed membrane/membrane apposition between nerve terminals and T cells in the spleen (15). Macrophages and B cells that reside in the marginal zone and outer marginal sinus also appear to be sympathetically innervated, while follicular B cells appear to be sparsely innervated.…”
mentioning
confidence: 99%
“…A maioria dos estudos sobre o efeito do estresse em contexto naturalista com humanos sugere que, em face de situações de estresse (por exemplo, a separação parental), o sistema imunológico exibe sinais de diminuição de competência decorrente da enervação dos tecidos linfáticos, tanto por projeções simpáticas como por projeções nervosas parassimpáticas 67 . Essa afetação implica uma diminuição da atividade dos linfócitos NK 68 ; a proliferação de linfócitos 69,70 ; a citocidade dos linfócitos 71 ; e um maior número de anticorpos aos vírus herpes 69,72 .…”
Section: Estresse E Imunologiaunclassified
“…Immunohistochemical studies show that there is the innervation of both primary and secondary lymphoid organs with sympathetic nerve fibers (10,11,(37)(38)(39), and that mast cells are also often found in the proximity of nerve fibers containing neuropeptides in a variety of tissues including skin, intestine, and dura mater (34,(40)(41)(42). Based on electron microscopic observation, nerve terminals are in direct apposition to T cells and mast cells.…”
Section: Coculture Systemmentioning
confidence: 99%